UJI EFEKTIVITAS BEBERAPA TANAMAN OBAT TERHADAP REPELENSI SERANGGA HAMA PERUSAK BERAS PADI VARIETAS CILIWUNG DI GUDANG BERAS - Krisna Antaboga; Bambang Supeno; Hery Haryanto (Fakultas Pertanian Universitas Mataram, 2023)
The purpose of this study was to determine the effectiveness of some plant material as insect repellence agents for rice pests Ciliwung variety. The methods used are field experiments and specimen collection. The research was carried out in one of the rice warehouses in Kuripan District and the Plant Protection Laboratory, Faculty of Agriculture, University of Mataram. The experiment was designed with a Group Randomized Design (GRD) consisting of six treatments. These treatments are; P0 (control), P1 (betel leaf; Piper crocatum), P2 (fragrant pandan leaves; Pandanus amarylifolius), P3 (bay leaf; Syzigium polyanthum), P4 (kaffir lime leaves; Citrus hystrix), and P5 (garlic bulbs; Alium Sativum). The results showed that betel leaf, fragrant pandan leaf, bay leaf, and kaffir lime leaf were effective against the rejection of three insect pests found. Three families of rice-destroying pests were found in Ciliwung varieties, namely; Family Tenebrionidae, Family Curculionidae, and Family Pyralidae. The plant materials used (betel leaf, fragrant pandan leaf, bay leaf, kaffir lime leaf, and garlic bulb) have no real effect on the diversity, dominance, and richness of Ciliwung variety rice pest species